Linear mixture modelling solution methods for satellite remote sensing - Hobbs, Stephen (Cranfield University, 2003)
This report documents the algorithms used in the program MIXMOD to analyse mixed pixel data (assuming linear mixing). The report describes the mathematical algorithms rather than acting as a user’s manual for MIXMOD. The algorithms described obtain the desired solutions, quantify the quality of the solution, and estimate error bounds, using a variety of methods. A novel feature is the ability to handle uncertainty in the assumed end-member spectra, which in practice may be the dominant source of error. The report includes a brief literature review to place the work in its broader context (with references to the mathematics of linear systems and other applications of mixture modelling in remote sensing
Keywords: Remote sensing; Linear mixture modelling; MIXMOD